CLINICAL AND EPIDEMIOLOGICAL PROFILES OF NOVEL VIRUSES IN LOWER RESPIRATORY TRACT INFECTIONS IN CHILDREN - Alexandru-Ioan Ulmeanu; Carmen Zapucioiu; Coriolan-Emil Ulmeanu (Amaltea Medical Publishing House, 2015)
Viral respiratory tract infections are one of the leading causes of morbidity and mortality in pediatric pathology. The authors provide the latest information on the structure, pathogenesis, clinical features, epidemiology and response to treatment of newly discovered viruses affecting the respiratory tract in children: bocavirus, metapneumovirus, coronaviruses, rhinovirus C.